Trained Peer Response to Develop EFL Students Positive Attitudes toward Peer Response - Utami Widiati (TEFLIN, 2003)
This article reports part of a broader action-research study on training EFL students in the use of strategies for effective peer response. Surveys using questionnaires were conducted among 20 university students involved in the action research to measure the changes in attitudes toward peer response before and after the classroom-based action research. The findings suggest that significant changes were obtained in all the questionnaire items regarding attitudes toward peer response. The students indicated that classmates oral and written comments helped them enrich the content of their writing, improve the organization of their writing, and improve the language (including grammar and vocabulary) of their writing.